2013
DOI: 10.1517/14740338.2013.806481
|View full text |Cite
|
Sign up to set email alerts
|

Phentermine and topiramate extended-release: a new treatment for obesity and its role in a complications-centric approach to obesity medical management

Abstract: Introduction: Weight-management options include lifestyle modifications, bariatric surgery and, until recently, limited pharmacotherapy. (phentermine/topiramate ER) has recently been approved in the USA for chronic weight management in obese adults and overweight adults with weight-related co-morbidities in conjunction with a reduced-calorie diet and increased physical activity.Areas covered: This review describes the pharmacology and clinical trials data for phentermine/topiramate ER and its role in a compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…These effects help patients sustain weight loss and help them comply with calorie‐reduced diets. Clinical trials have shown that the addition of pharmacotherapy to lifestyle interventions promotes greater weight loss and sustains weight loss for a longer period of time than lifestyle interventions alone 13, 96, 97, 99, 100, 116. The available data, while only encompassing ≤2 years of follow‐up, demonstrate that these pharmacotherapies sustain weight loss while patients randomized to lifestyle interventions plus placebo are regaining weight (Table 1) 13, 96, 97, 99, 100, 116.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…These effects help patients sustain weight loss and help them comply with calorie‐reduced diets. Clinical trials have shown that the addition of pharmacotherapy to lifestyle interventions promotes greater weight loss and sustains weight loss for a longer period of time than lifestyle interventions alone 13, 96, 97, 99, 100, 116. The available data, while only encompassing ≤2 years of follow‐up, demonstrate that these pharmacotherapies sustain weight loss while patients randomized to lifestyle interventions plus placebo are regaining weight (Table 1) 13, 96, 97, 99, 100, 116.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Phentermine/topiramate ER is an oral combination of immediate-release phentermine hydrochloride and ER topiramate (25). Phentermine is a sympathomimetic amine anorectic agent approved in 1959 for the short-term treatment of obesity at a dose of 30 mg (free base) by mouth once a day.…”
Section: Recently Approved Weight-loss Medicationsmentioning
confidence: 99%
“…Although the drug augments gabaminergic transmission, inhibits α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor/kainite excitatory glutamate receptors and has carbonic anhydrase activity, the mechanism by which topiramate causes weight loss is unknown. Phentermine/topiramate ER combines lower doses of phentermine and an ER form of topiramate in a once-daily pill to achieve synergism with respect to weight loss at lower adverse event rates when compared with higher doses of these individual medications (25). …”
Section: Recently Approved Weight-loss Medicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bariatric surgery can be highly effective for weight-loss, but access for patients can be limited due to long wait lists, high costs and variable follow-up care (34). Additionally, the invasive nature of surgery can result in a range of adverse events and mortality related to the procedures (34,35). Pharmaceuticals and bariatric surgery are also infrequently recommended by physicians as a weight loss approach (36).…”
Section: Clinical Treatmentmentioning
confidence: 99%